2019
DOI: 10.1111/1756-185x.13730
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods of quantifying global synovial metabolic activity with FDG‐PET/CT in rheumatoid arthritis

Abstract: Aim: 2-deoxy-2-[ 18 F]fluoro-d-glucose positron emission tomography/computed tomography (FDG-PET/CT) can portray increased glycolysis due to inflammation in rheumatoid arthritis (RA). The aim of this study was to evaluate and compare the reliability and construct validity of two methods of quantifying RA disease activity using FDG-PET/CT. Method:Nineteen RA patients and 19 healthy controls matched to sex and age underwent prospective FDG-PET/CT imaging. Metabolic and volumetric metrics were calculated using fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Data from the approach have similarly demonstrated great importance in patients with cancer, atherosclerosis, systemic inflammation, and musculoskeletal disorders. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18
Fig. 2 Maximum intensity projection (MIP) FDG PET/CT scans of a 60-year-old patient with multiple myeloma ( A ) pretreatment 1 hour and ( B ) pretreatment 3 hours after administration of FDG.
…”
Section: Practical Clinical Applicationsmentioning
confidence: 99%
“…Data from the approach have similarly demonstrated great importance in patients with cancer, atherosclerosis, systemic inflammation, and musculoskeletal disorders. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18
Fig. 2 Maximum intensity projection (MIP) FDG PET/CT scans of a 60-year-old patient with multiple myeloma ( A ) pretreatment 1 hour and ( B ) pretreatment 3 hours after administration of FDG.
…”
Section: Practical Clinical Applicationsmentioning
confidence: 99%
“…FDG is a glucose analog whose cellular uptake is proportional to the metabolic activity of the cells. The value of FDG in the diagnosis of inflammation as well as malignancy is well established, and FDG PET/CT is used in rheumatologic diseases such as rheumatoid arthritis, vasculitis, and polymyalgia rheumatica [37][38][39][40]. Recently, its use in IIMs has also been described, and researchers have demonstrated higher SUVs in patients than controls [25,29] or persons with non-inflammatory muscle disease [41], but also an overlap of FDG uptake in patients with IIM and without [31].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the feasibility of whole-body PET to assess disease activity in patients with RA. 12,[21][22][23][24][25][26] Most studies have used FDG as tracer, which is sensitive but not specific for imaging arthritis. Some studies have looked only at visually enhanced uptake, whereas in other studies, quantitative analyses were performed.…”
Section: Discussionmentioning
confidence: 99%